A Heuristic Approach To The Index Tracking Problem: A Case Study Of The Tehran Exchange Price Index - Varsei, Mohsen; Shams, Naser; Fahimnia, Behnam; Yazdanpanah, Abbas (Asian Academy of Management (AAM), 2013)
Index tracking, the most popular form of passive fund management, is a portfolio selection problem in which the return of one of the stock market indexes is reproduced by creating a tracking portfolio consisting of a subset of the stocks included in the index. Index tracking has been known as an NP-Hard problem, and sophisticated approaches have been proposed in the literature to solve this problem. This paper presents an easyto-implement heuristic solution to this complex problem. The proposed approach was implemented to develop a tracking portfolio of 438 stocks listed in the Tehran Exchange Price Index. The numerical results indicate that the approach is able to identify quality solutions within reasonable model runtime.